(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To compare the outcomes of ureteroscopic lithotripsy with pneumatic lithotripter versus Holium:Yttrium-Aluminum-Garnet (Ho:YAG) laser in the management of upper ureteric stones. Materials and methods: Patients who underwent ureteroscopic lithotripsy with pneumatic lithotripter or Ho:YAG laser for upper ureteric stones were reviewed. Patients with urinary tract infection, ,loss of follow-up, concurrent middle or lower third ureteral stones or acute renall failure were excluded. Patient age, stone size and burden (based on KUB or computerized tomography), stone upward migration, double J stent insertion rate, stone free rate and secondary intervention rate for residual stones were compared in both groups. Results: There were 70 patients with upper ureteric stones (35 in pneumatic group and 35 in laser group) meeting the study criteria. Patients’ age, gender, stone size and burden were similar in both groups. The Ho:YAG laser lithotripsy group had better stone free rate, less double J stent insertion rate and less upward migration and secondary intervention rate, sepsis as compared with pneumatic lithotripsy (94.2% vs. 60%; 85% vs. 100%; 5.7% vs 40%; 5.7% vs 34.2%; 2.8 vs 2.8 respectively, all p < 0.05). In patients with stones sizes 8-10 mm, Ho:YAG laser lithotripsy had significantly lower upward migration rate, lower double J stent insertion rate, higher stone free rate and less secondary intervention rate. Conclusions: Ho:YAG laser lithotripsy is better and much effective than pneumatic lithotripsy in the management of upper ureteric stones in terms of, stone free rate and secondary intervention rate for stones of sizes about 8 to 10 mm.Although the access of upper ureter is difficult but our small calibre (4.5 fr) ureteoscope and gentle manuevre have made the procedures safe and successful. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.188-192